2016
DOI: 10.1159/000453185
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Indicating Value of Cardiac Troponin I, Tumor Necrosis Factor-α, Interleukin-18, Mir-1 and Mir-146b for Viral Myocarditis among Children

Abstract: Background/Aims: The primary objective of this study is to evaluate the diagnosis effect of serum protein factors and microRNAs for children suffering from viral myocarditis (VMC). Methods: The expression levels of serum cardiac troponin I (cTnI), interleukin-18 (IL-18) and tumor necrosis factor-α (TNF-α) in both VMC and control groups were examined by using the Elisa Kit. The expression levels of miR-1 and miR-146b were measured through RT-PCR. Subsequently, the Receiver Operating Characteristic (ROC) curves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 37 publications
(38 reference statements)
0
15
0
1
Order By: Relevance
“…It plays key roles in inflammatory and immune responses and has significant influence on the pathogenesis of diseases (Lukens et al 2012). Up-regulated serum IL-18 level was also reported in sepsis (Feng et al 2016), asthma (Xu et al 2017), and viral myocarditis (Wang et al 2016) and was reported to be involved in intestinal inflammation (Sivakumar et al 2002;Siegmund 2010) and colitis (Kanai et al 2001;Ishikura et al 2003).…”
Section: Discussionmentioning
confidence: 94%
“…It plays key roles in inflammatory and immune responses and has significant influence on the pathogenesis of diseases (Lukens et al 2012). Up-regulated serum IL-18 level was also reported in sepsis (Feng et al 2016), asthma (Xu et al 2017), and viral myocarditis (Wang et al 2016) and was reported to be involved in intestinal inflammation (Sivakumar et al 2002;Siegmund 2010) and colitis (Kanai et al 2001;Ishikura et al 2003).…”
Section: Discussionmentioning
confidence: 94%
“…There is no significance of the expression of serum miR-146b among 5 AIS groups in this study (data not shown), which may suggest that miR-146b may be a biomarker for AIS but not for separating subtypes of AIS. In fact, miR-146b is one of the most-studied miRs [32,33], and especially in the vascular smooth muscle cell (VSMCs) proliferation, differentiation, and phenotypic switching. In cardiovascular system, miR-146b is not only important for heart and vascular development but also plays an essential role in cardiac pathological factors, such as hypertrophy and ischemia, and has been regarded as a new therapeutic target for vascular disease [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-1 decreased significantly in VMC, which was negatively correlated with the left ventricular shortening fraction and left ventricular ejection fraction. MiR-146b was significantly up-regulated in VMC, which was positively correlated with those two indexes (Wang D. et al, 2016 ). Therefore, miR-1 and miR-146b may be potential disease markers of VMC.…”
Section: The Role Of Mirnas In Cvb3-induced Vmcmentioning
confidence: 96%